Magnetosphere-Ionosphere Coupling: Implications of Non-Equilibrium Conditions - Lockwood, Mike; Cowley, Stan W. H. (Frontiers in Astronomy and Space Sciences, 2022)
The response times of the coupled magnetosphere-ionosphere-thermosphere system are considerably greater than the autocorrelation timescales of solar wind forcing. This means that the system is rarely, if ever, in equilibrium. Departures from equilibrium are a key component of the Expanding-Contracting Polar Cap (ECPC) model of convection excitation in both the magnetosphere and ionosphere, driven by the Dungey reconnection cycle of opening and re-closing magnetospheric field lines. Averaging over sufficiently long timescales reduces data to the equivalent of steady-state conditions, which hides the physical mechanisms involved and allows us to map electric fields from interplanetary space to the ionosphere in a way that is not valid, either physically- or generally-speaking, because of induction effects. Only for transient phenomena on sufficiently short timescales, do the mechanisms associated with non-equilibrium fully manifest themselves. Nevertheless, because of both changing solar wind conditions and Earth’s rotation, the magnetosphere is always tending towards a perpetually-evolving equilibrium configuration and there are important implications of transient events for understanding general behavior of the coupled magnetosphere-ionosphere-thermosphere system and its response to solar wind forcing. We here discuss one example: as a consequence of the importance of departures from equilibrium inherent in the ECPC model, the solar wind dynamic pressure Psw influences the magnetosphere-ionosphere convection response to the generation of open field lines by reconnection in the dayside subsolar magnetopause. We here demonstrate this effect in a statistical survey of observations and show that it is as predicted by the ECPC model and that, through it, Psw has an influence on flux transport in the magnetosphere-ionosphere system.